New features of magnetoresistance in the strongly anisotropic layered metals - Grigoriev, P.D. (Физика низких температур, 2011)
The angular and magnetic-field dependence of interlayer magnetoresistance is calculated in the limit of strong magnetic field and very high anisotropy, where it shows several unusual properties. The monotonic part of interlayer magnetoresistance grows with the increase of magnetic field along the current, which contradicts the standard theory. This changes the angular dependence of magnetoresistance. The Dingle temperature increases with magnetic field, which damps the magnetic quantum oscillations and changes the field dependence of their amplitudes.